ФУҚАРОЛИК ЖАМИЯТИНИ ШАКЛЛАНТИРИШ ВА РИВОЖЛАНТИРИШДА МАҲАЛЛИЙ ЎЗИНИ ЎЗИ БОШҚАРИШ ОРГАНЛАРИНИНГ ЎРНИ - Ишқуватов, В. (SCIENCE and SOCIETY, 2020)
The article is devoted to the needs of forming a civil society at the level of state policy in the scope of self-government bodies in Uzbekistan, the activities of the mahalla and its current needs. At the same time, it outlines the existing problems in this area and the work done by self-governing bodies and organizations to solve them.